2014
DOI: 10.1080/00222895.2014.961890
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Implicit Sequence Learning in Persons Who Stutter and Persons With Parkinson's Disease

Abstract: The authors investigated the retention of implicit sequence learning in 14 persons with Parkinson's disease (PPD), 14 persons who stutter (PWS), and 14 control participants. Participants completed a nonsense syllable serial reaction time task in a 120-min session. Participants named aloud 4 syllables in response to 4 visual stimuli. The syllables formed a repeating 8-item sequence not made known to participants. After 1 week, participants completed a 60-min retention session that included an explicit learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…In our study, apparently the amount of training, i.e., 160 repetitions of the sequence, was sufficient for AWS to catch up to ANS. This is in line with other studies that report that AWS can perform at a comparable level as ANS after a substantial amount of repetitions ( Smits-Bandstra and Gracco, 2013 , 2015 ). A larger number of repetitions is needed by AWS to catch up to the performance of ANS ( Cooper and Allen, 1977 cited in Smits-Bandstra et al, 2006b ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, apparently the amount of training, i.e., 160 repetitions of the sequence, was sufficient for AWS to catch up to ANS. This is in line with other studies that report that AWS can perform at a comparable level as ANS after a substantial amount of repetitions ( Smits-Bandstra and Gracco, 2013 , 2015 ). A larger number of repetitions is needed by AWS to catch up to the performance of ANS ( Cooper and Allen, 1977 cited in Smits-Bandstra et al, 2006b ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, limitations in the speech skill of stuttering individuals could emerge due to the limited ability to learn motor sequences. In line with this suggestion, studies have reported poorer speech sequence skill learning in adults who stutter (AWS) than in those who do not (ANS; Smits-Bandstra et al, 2006b ; Namasivayam and van Lieshout, 2008 ; Smits-Bandstra and De Nil, 2009 ; Smith et al, 2010 ; Bauerly and De Nil, 2011 ; Smits-Bandstra and Gracco, 2013 , 2015 ; Sasisekaran and Weisberg, 2014 ). Other studies have used finger tapping tasks to investigate if limitations in motor sequence learning or performance also affect non-speech movements in AWS ( Webster, 1986 ; Smits-Bandstra et al, 2006a , b ; Bauerly and De Nil, 2015 ).…”
Section: Introductionmentioning
confidence: 78%
“…Two more recent studies highlight differences in retention for Parkinson's disease patients. An initial test of sequence learning was not affected in Parkinson's disease, though patient retention a week later was [55]. Patients tested on an implicit learning sequence task performed as well as healthy controls in a first block, but not in a second block [56].…”
Section: Learning Deficits In Parkinson's Diseasementioning
confidence: 92%
“…Of course, given that PD patients have obvious movement difficulties and tremors, one might not be surprised by an impairment in a task that involves rapid button pressing. Some studies have shown reduced learning in PD when a verbal response is required (see Clark et al., 2014), while others have shown intact learning (Smith et al., 2001), or even the emergence of learning in a second training session after a 1‐week interval (Smits‐Bandstra & Gracco, 2015). The reason for such discrepancies is not clear.…”
Section: Sequence Learningmentioning
confidence: 99%